PENGEMBANGAN MODUL BERBASIS DISCOVERY LEARNING PADA MATERI GETARAN DAN GELOMBANG DI SMPN 4 JAYAPURA - Pali, Kristina; Virman, Virman; Budiarti, Indah Slamet (Papua Journal of Physics Education, 2023)
This study is related to the development of teaching materials that adapt the changes in the old curriculum to the new curriculum, namely the 2013 curriculum by implementing a learning model, namely a discovery learning-based module. The Discovery learning model is one model that can play a role in solving problems for students so that they can learn independently. The purpose of this study is to see the feasibility and response of students regarding the discovery learning-based module. This researcher adapted from the ADDIE development model (Pribadi, 2014) which has 5 stages. However, in this study it was only limited to the development stage so that only 3 stages were carried out, namely Analysis, Design, and Development until a limited trial was carried out. Module validation was carried out by 3 validators to test 6 aspects that were assessed and obtained an overall percentage of 88.08% with a very strong interpretation and a limited trial to 31 class VIII A students where seen from the 4 aspects that were assessed obtained an overall percentage of 92% with a very strong implementation. So based on these results, it can be concluded that the discovery learning-based learning module on the subject of vibrations and waves at SMPN 4 Jayapura is suitable for use and the response of students regarding the discovery learning-based module for the subject of vibrations and waves is very good